PENERAPAN STRATEGI BISNIS MODERN PADA LEMBAGA BISNIS PUBLIK - Andi Indra Martini (AkMen JURNAL ILMIAH, 2011)
Along with the development era of globalization and modernization of foreign each firm both public and private to review the business strategy who have applied so they can continue to survive and complete in the world of business.Public institution as well as business assets of the state should continue to improve its performance by reforming si that it can synergize in a healthy business in accordance with the rules and regulations.